The world and Europe in the eyes of Turkish undergraduate students - France Guérin-Pace; Etienne Toureille; Claude Grasland (Belgeo)
The recent history of Turkey is characterised by major changes in public discourse and public opinion, related to the changing position of Turkey on the world stage. Changing attitudes toward European Union appear to be a marker of this transformation. The aim of this paper is to evaluate the perception of Europe and the world in the eyes of Turkish undergraduate students through a secondary analysis of a worldwide survey carried out in 2009-2010 by the FP7 EuroBroadmap project. The paper proposes first to test the hypothesis of a polarisation of Turkish representation by the European Union against the alternative hypothesis of a dual vision of Europe related to the ambiguity of Turkey’s situation. This part concludes that western and south European countries (like Italy, France, Britain and Spain), were still very positively viewed by Turkish students in 2009 and constitute a structuring pole of their worldwide representations. But the paper also examines variations in these average mental maps according to individual parameters. This second analysis reveals huge internal variations, according to place, gender and field of study and confirms that visions of the world held by students in this country are neither trivial nor consensual.